Exploring Vocabulary Self-collection Strategy (VSS) Learning of EFL Junior High School Students in Vocabulary Classes - Alnoer, Allysa Putri; Pahlevi, M. Reza; Fitriyana, Wahyudin (Peneliti.net, 2023)
Students often do not understand or know the meaning of foreign language vocabulary, especially English. Usually, they only learn English vocabulary from the material the teacher taught them. Therefore, this study explores another teaching strategy, the vocabulary self-collection strategy (VSS). This study employs qualitative research and descriptive case studies. The study involved with 33 participants. However, of the 33 volunteers recruited, 6 were recruited for interviews. Use thematic analysis as well as data analysis techniques. The results show that VSS serves learning activities that make students self-directed learners, encouraging them to learn new vocabulary with enthusiasm. On the other hand, student collaboration in learning becomes a challenge because it requires collaboration. In conclusion, VSS is a potential instructional strategy to support and equip students to learn vocabulary correctly.